2010
DOI: 10.1097/fbp.0b013e32833befe5
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like properties of phosphodiesterase type 5 inhibitors and cholinergic dependency in a genetic rat model of depression

Abstract: We explored the antidepressant-like properties of two phosphodiesterase type 5 (PDE5) inhibitors in a genetic animal model of depression, namely Flinders sensitive line rats. We investigated the dose-dependency of the antidepressant-like action of sildenafil, and its interaction with the cholinergic system and behavioural correlates of monoaminergic neurotransmission, in the forced swim test. Antidepressant-like properties of tadalafil (a structurally distinct PDE5 inhibitor) were also evaluated. Flinders sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 53 publications
0
45
0
1
Order By: Relevance
“…In an earlier study they found that the ability of these inhibitors to have AD-like effects depended on cholinergic tone, with a blocker like atropine facilitating AD-like effects. Their study with the FSL rats confirmed this relationship but also demonstrated that chronic treatment with two phosphodiesterase inhibitors, sildenafil and tadalafil, induced anxiolytic effects (Liebenberg et al, 2010.…”
Section: Recent and Current Researchmentioning
confidence: 64%
“…In an earlier study they found that the ability of these inhibitors to have AD-like effects depended on cholinergic tone, with a blocker like atropine facilitating AD-like effects. Their study with the FSL rats confirmed this relationship but also demonstrated that chronic treatment with two phosphodiesterase inhibitors, sildenafil and tadalafil, induced anxiolytic effects (Liebenberg et al, 2010.…”
Section: Recent and Current Researchmentioning
confidence: 64%
“…128 Further, chronic treatment with sildenafil, a phosphodiesterase type 5 (PDE5) inhibitor, decreased immobility in the FSL rats. 120 Thus, the treatment impacting directly on one of the intracellular signalling systems appeared to be sufficient to normalize the «de-pressive» behaviour in FSL rats. Increased levels of arachidonic acid-containing phosphatidylcholine (AA-PC) species were found in the hypothalamus and striatum of the FSL rats, and there were decreased levels of the docosahexaenoic acid (DHA)-containing species in the striatum and prefrontal cortex.…”
Section: Alterations Of the Second Messenger Signalling Systems In Thmentioning
confidence: 99%
“…119 Different behavioural features of the FSL model, immobility in the forced swim being the most often tested, have been either normalized or at least affected (sildenafil 120 ) following chronic, but not acute, treatment with tricyclic antidepressants (imipramine; …”
Section: Predictive Validity Of the Fsl Model Of Depressionmentioning
confidence: 99%
“…I) Cognition. In a study of memory consolidation in animal models, PDE5 inhibitors, like a number of other PDE inhibitors, improve cognitive function (194,309,310,331,386) and exhibit antidepressant effects (208). Vardenafil enhances early phase consolidation independent of its effects on cerebral vasculature (309,310).…”
Section: Expanded Uses For Approved Pde5 Inhibitorsmentioning
confidence: 99%